Evaluation of the efficacy of hydro-alcoholic products for hand skin disinfection: Case study Bactigel® used in the Livulu district of Lemba, Kinshasa City (Democratic Republic of Congo) (International Journal of Agricultural Research, Innovation and Technology, 2024)
Preventing, reducing, and improving infection control have been struggles that have preoccupied the World Health Organization for many years. The present study aims to evaluate the efficacy of Bactigel hydro-alcoholic gel on the cutaneous flora of hands. The study was conducted by interviewing people on their knowledge and use of hydro-alcoholic products and culture of palm flora samples before and after hand disinfection. Results showed that 90% of respondents knew about hydro-alcoholic products, 96.3% of whom had already used them, and 92.3% were still used. In addition, 90% do not have alcohol-sensitive skin, and 80% use soap and water with soap for hygiene in their homes. Bactigel significantly reduced the microbial load on palms by 90.04%. Based on these results, Bactigel hydro-alcoholic gel is effective against skin germs. It is concluded that Bactigel can only be effective in the community when compliance is good hand hygiene.Int. J. Agril. Res. Innov. Tech. 13(2): 49-54, Dec 2023